Beyond voluntary consent: Hans Jonas on the moral requirements of human experimentation - Fethe, C. (Journal of medical ethics, 1993)
In his essay, Philosophical Reflections on Experimenting with Human Subjects, Hans Jonas contends that except in cases of widespread medical emergencies, people do not have a moral or social obligation to volunteer to be subjects in medical experiments. He further argues that any appeal for volunteer subjects in medical experiments should whenever possible give priority to those who can identify with the project and offer a strong sense of commitment to its goals. The first of these claims is given support against some recent criticisms, but argument is offered to show that the second claim not only does little to enhance the stature of the standard requirement of free and informed consent but may even weaken the moral validity of the consent.